Remarkable Enhancement of Growth and Yield of Rice at a Farmer’s Field by Applying Sesbania Debris According to a New Technique - Pongsiri Patcharapreecha; Duangsamorn Taja; Hiroshi Ishida; Hidenori Wada (Agriculture and Natural Resources, 1992)
At harvest-time, detailed examination was made on growth and yield of rice growing in a rain-fed farmer’s paddy field to clarify effects of the surface-placement of sesbania debris prior to incorporation into the submerged soil. Four plots were set up in the field. The C plot was applied with ammonium sulfate (12 kg N/rai). The S and 2S plots were applied with sesbania debris at the rate of about 12 kg and 24 kg N/rai, respectively. The Ch plot was unfertilized. As compared with the Ch plot, the green manuring increased culm length, ear number, straw weight, ear weight and yield. This was especially remarkable for 2S plot. Among yield components, ear number and/or grain number per ear greatly contributed to yield increase in the S and 2S plots. Increase in both percentage of selected brown rice and thousand-kernel-weight were contributed to increases in yield in the S and 2S plots also. On the contrary, growth and yield of rice in the C plot was not much different from those in the Ch plot. These results also showed that rice plants in the S and 2S plots were healthy and vigorous in the later growth stage. Uptake of macro-nutrients by rice plants was enhanced by the green manuring but not by application of ammonium sulfate. Implication of these results were discussed.